Social media utilization, mindfulness practice, and psychological distress of nonprofit workers in China: mediation effects of positive and negative affect - Qianyi Tu; Chienchung Huang; Bin Tu (Frontiers in Public Health)
IntroductionIn the contemporary landscape, the intersection of technology and human behavior has given rise to transformative trends, prominently featuring the emergence of social media. Nevertheless, studies show that adults who heavily depend on these platforms may affect their psychological distress. Conversely, a growing body of research indicates that engaging in mindfulness practices can regulate emotional reactions and contribute to enhanced mental health, resulting in a reduction of psychological distress.MethodsIn this investigation, a cross-sectional survey involving 318 adult nonprofit employees in China was conducted to explore the impact of social media utilization and mindfulness practice on psychological distress. The study specifically aimed to examine whether positive and negative affect mediate the relationships between these variables. Structural Equation Modeling was employed to analyze both the direct and indirect effects of social media utilization and mindfulness practice on psychological distress through positive affect (PA) and negative affect (NA).ResultsSocial media utilization positively influenced positive affect (PA) (β = 0.15, p < 0.01) but showed no significant impact on negative affect (NA). Mindfulness practice displayed a positive effect on PA (β = 0.30, p < 0.001) and a negative effect on NA (β = −0.10, p < 0.10). PA exhibited a negative effect on psychological distress (β = −0.12, p < 0.01), whereas NA had a positive effect on psychological distress (β = 0.75, p < 0.001). The total effect of mindfulness practice on psychological distress was −0.11 (p < 0.01), while social media utilization did not have a significant effect on distress.DiscussionsThe results indicated that participating in mindfulness practice boosts PA and simultaneously diminishes NA and psychological distress. Despite social media utilization being linked to heightened PA, it did not demonstrate significant effects in mitigating NA or psychological distress. This study underscores the significance of advocating for mindfulness practice as a public health strategy to alleviate NA and psychological distress, while also fostering PA among adults in China.